HISTRIONIC IMMATURE PERSONALITY DISORDER - Trifu, Simona; Neacșa, Elena-Alexandra; Neagoe, Ștefania-Elena; Ojică, Andreea-Simina (International Journal of Research -GRANTHAALAYAH, 2021)
Background: We aim at presenting a clinical case of a 37-year-old patient, who has been a nun for several years and at the moment can no longer adapt to the environment in which she lives and to the requirements of everyday life. The perspective of this analysis is both a psychiatric one, explaining the diagnosis of Axis II of Histrionic Immature Personality Disorder, but also the overlap with dissociative conversion disorder, and explanatory from a psychodynamic perspective, by addressing the regression issues and the presence of the Oedipus Complex. Histrionic Immature Personality Disorder and its overlap with Dissociative/Conversion Disorder are conditions with negative effects in terms of adaptation to the social environment and assuming professional responsibilities. Also, the particularities in the sphere of immaturity make it difficult to relate to those around. Method: Hospitalization, psychiatric interview, psychodynamic interview, psychological tests - CAQ Personality Questionnaire and the Szondi Test, psychodynamic interpretations. Results: The results highlight aspects of an immature premorbid personality, characterized by a high degree of sensitivity. Currently, the patient's ego is fragile and cannot adapt to the emotional meanings in the environment in which she lives, which leads to functional crises and manifestations such as dissociative fugue. Conclusions: Dissociative manifestations are associated with immaturity and reduced ability to adapt to professional requirements. On a personal level, the same immaturity leads to the denial of one's sexuality and projection.